Walter Day: The First Video Game Religious Pilgrim - Banasik, Benjamin Jozef (Fieldwork in Religion, 2020)
This article examines the life of Walter Day, a key figure in the history of competitive video gaming and whose involvement in this industry has been connected to his own spiritual beliefs and directions. Here, the influence of Day, the former owner of Twin Galaxies and creator of the first International Scoreboard, will be presented by examining the history of his life. A pivotal religious experience of Day, while under the influence of LSD in the 1960s, will be shown to have directly informed his decision to join the Eastern influenced new religious movement of Transcendental Meditation under the stewardship of Maharishi Mahesh Yogi which gave him the tools and direction that would be essential for his video gaming career. The training that the Maharishi would provide to Day will be explored and shown to have informed his understanding of religious experiences, or flow states, and how this could manifest with a player of a classic video game at an arcade. This understanding will be shown to have interested Day enough not only to endeavour to be the first video game pilgrim, but for him to continue a lifelong pilgrimage of recording and sharing oral history of players who reach their full potential.